Secukinumab Therapy on Psoriasis at Dr. Mohammad Hoesin General Hospital Palembang - Nopriyati; Rio Tampubolon; Sarah Diba; M Athuf Thaha; Theresia L Toruan; Fitriani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Psoriasis is a chronic inflammatory skin disease mediated by T lymphocytes. IL-17 or IL-22 plays an important role in the chronic inflammatory process. Secukinumab is an effective biological agent therapy with a molecular target, IL-17A. This study aimed to describe PASI improvement and safety of using secukinumab in psoriasis patients at the Dermatology and Venereology Clinic Dr. Mohammad Hoesin General Hospital Palembang. Methods: This study was a retrospective, descriptive-analytic study. The inclusion criteria of this study were all medical record data of patients diagnosed with cutaneous psoriasis through anamnesis, clinical and histopathology examination, treated with secukinumab from January 2018 to December 2020. Results: Psoriasis patients with secukinumab therapy were 15 people. The number of male patients was 8 people, the mean age (+ SD) was 40.4, + 12.34 years, and the age range was 19-64 years. A family history of psoriasis was present in 2 patients (13.4%). Psoriasis vulgaris was the most prevalent type of psoriasis and was treated with secukinumab in 8 patients (53.3%). Another type was pustular psoriasis (20%) and erythrodermic psoriasis (26,7%). The triggers of exacerbations obtained in this study include occupation, hypertension, diabetes mellitus, obesity, smoking, and infections. PASI 75 was achieved by 13 patients (86.7%) at week 12, and all patients achieved DLQI<5. There were no adverse events during the use of secukinumab. Conclusion: The improvement of PASI and DLQI scores were achieved at week 12 in accordance with previous studies. Risk factors do not reduce the therapeutic effect of secukinumab in achieving PASI 75.